2023
DOI: 10.3389/fpls.2023.1105079
|View full text |Cite
|
Sign up to set email alerts
|

Targeting market segment needs with public-good crop breeding investments: A case study with potato and sweetpotato focused on poverty alleviation, nutrition and gender

Abstract: Crop breeding programs have often focused on the release of new varieties that target yield improvement to achieve food security and reduce poverty. While continued investments in this objective are justified, there is a need for breeding programs to be increasingly more demand-driven and responsive to the changing customer preferences and population dynamics. This paper analyses the responsiveness of global potato and sweetpotato breeding programs pursued by the International Potato Center (CIP) and its partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…For example, women in Uganda have a unique role to select and prepare food for household consumption, constitute a big proportion of sweetpotato farmers and retailers and own small-scale businesses including local restaurants and food shelters. 30 Breeding sweetpotato for sensory characteristics would ease food preparation, and enhance profit margins by increasing their market share. 30 Generally, consumers in Kamuli showed a more positive response to the samples than those in Hoima as indicated by the higher consumer liking ratings and bigger proportion of respondents perceiving samples to have appropriate intensities of sweetness, firmness and mealiness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, women in Uganda have a unique role to select and prepare food for household consumption, constitute a big proportion of sweetpotato farmers and retailers and own small-scale businesses including local restaurants and food shelters. 30 Breeding sweetpotato for sensory characteristics would ease food preparation, and enhance profit margins by increasing their market share. 30 Generally, consumers in Kamuli showed a more positive response to the samples than those in Hoima as indicated by the higher consumer liking ratings and bigger proportion of respondents perceiving samples to have appropriate intensities of sweetness, firmness and mealiness.…”
Section: Discussionmentioning
confidence: 99%
“…30 Breeding sweetpotato for sensory characteristics would ease food preparation, and enhance profit margins by increasing their market share. 30 Generally, consumers in Kamuli showed a more positive response to the samples than those in Hoima as indicated by the higher consumer liking ratings and bigger proportion of respondents perceiving samples to have appropriate intensities of sweetness, firmness and mealiness. The proportion of consumers who perceived none of the sweetpotato genotypes to be excessive in sweetness, firmness or mealiness was small as illustrated by the JAR scale findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The puree yields healthier products since its preparation involves more nutrientconserving methods such as steaming/boiling than smashing the OFSP, which retain ⊎-carotene content at about 90%, with enhanced color and desired microbial properties that preserve the quality of baked products. 6,7 According to Malavi et al, 8 incorporating OFSP puree into baked products like bread improves their texture, making them easier to chew and digest. Moreover, studies in the SSA region have shown that it is economically feasible to use OFSP puree as a substitute for wheat flour compared to OFSP flour.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it reduces the amount of money spent on wheat flour. The puree yields healthier products since its preparation involves more nutrient‐conserving methods such as steaming/boiling than smashing the OFSP, which retain β‐carotene content at about 90%, with enhanced color and desired microbial properties that preserve the quality of baked products 6,7 . According to Malavi et al ., 8 incorporating OFSP puree into baked products like bread improves their texture, making them easier to chew and digest.…”
Section: Introductionmentioning
confidence: 99%